السياسة الشرعية الاقتصادية عند الخليفة عثمان بن عفان رضي الله عنه (دراسة تحليلية مقاصدية)= Assiyasah Sysyariyyah Al-Iqtishodiyah 'Indal Khaifah Itsman Bin Affan Radhhiallohu'anhu - Bakar, Umarul Faruq Abu; , Dr. M. Muinudinillah Basri, M.A; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
This thesis is applied for Islamic Law Master Program, Muhammadiyah University of Surakarta. Arranged by: Umarulfaruq Abubakar. NIM: O 0001 100 30. Supervised by: Dr. Muhammad Mu'in Dinillah Bashri, MA and Dr. Muhammad Abdul Khalik Hasan. Year : 2014 AD - 1436 H. The period of Khalifah Utsman bin Affan's Goverment is well known by its advancement economy. Khalifah Utsman successfully managed the Islam countries' potential; so that the government in that period was able to give the citizenry prosperity. That is why it is interesting to conduct a study related to the economic policy in the period of Khalifah Utsman Bin Affan Radhiallahu Anhu's government. This study used qualitative method in form of document analysis. In this study, the researcher focused on the three problems. They are 1) how was the Economic policy of Kalifah Ustman bin Affan? 2) What was the genius side of Ustman bin Affan's politic choices? 3) How is our way to argue the bad accusations toward Ustman bin affan in every problem such as the appointment of his family as the governor and treating his family better than treating others Muslims? After conducting the research through some literatures, the researcher concluded that: 1) The Kalifah Utsman bin Affan's economic policy applied the principles of Islamic law which same as the application of Rasulullah and the previous two khalifas ( Abu Bakar Ash Sidiq and Umar bin Khatab) by some difference policies in the management of Zakat, Fai' and society subsidy. 2) Khalifah ustman bin affan was able to maximize the general revenue and expenditure budget based on the society's needs in that era until engendering society prosperity and the healthy economic behavior. 3) The Khilafah Ustman's policy persistently holding on the principles of trusteeship, justice and placing the public functionaries based on their capabilities. The charity he gave to his family derived from his own wealth and the member of his family who became the public functionaries was pointed by the previous Khalifah Abu bakar and Umar and they had good leaderships.